Allergic march in childhood - Duczmal, Ewa; Bręborowicz, Anna; Duczmal, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : The allergic march is defined as a natural history of atopic diseases, such as allergic dermatitis, food allergy, allergic rhinitis and asthma, in which one clinical manifestation precedes and predicts another. The opposing theory, the coexistence of allergic diseases, is an equally popular alternative. Aim: To assess the course of allergic diseases and the influence of different factors on the occurrence of allergic march in childhood. Material and methods: In a retrospective study 273 patients with allergic diseases were included. The course of the disease, in the retrospective study, was evaluated on the basis of questionnaires, health books and documentation of vaccinations. Results : In the retrospective study, allergic march was observed in 74% of patients, from which 38% manifested classical march and 36% the different march. Atopic dermatitis preceded asthma in 49.5% of patients with the allergic march phenotype. Environmental factors influencing the development of the allergic march phenotype have not been identified. Patients exposed to passive smoking during pregnancy (OR 2.60, 95% CI 1.03–6.57, p = 0.038) had greater prevalence of the classical march, whereas the different march was observed more often in patients from complicated pregnancies (OR 0.55, 95% CI 0.31–0.96, p = 0.036). Conclusions: Most children with allergic diseases have allergic march in childhood.